2020
DOI: 10.1002/jbmr.4245
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Megakaryocyte-Driven Osteosclerosis in Mpig6b-Deficient Mice Is Sex-Linked

Abstract: Patients with chronic myelofibrosis often suffer from osteosclerosis, which is associated with bone pain and may lead to bone marrow failure. The pathogenesis of myelofibrosis is linked to aberrant megakaryocyte development and function. Null and loss‐of‐function mutations in MPIG6B, which codes for the inhibitory heparan sulfate receptor G6b‐B, result in severe macrothrombocytopenia, large megakaryocyte clusters, and focal primary myelofibrosis in mice and humans. We investigated the development of osteoscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…3–7 Our results demonstrate a previously unrecognized key function of G6b-B in MK maturation by regulating cell size, DMS development, receptor levels and gene expression. These findings thus challenge the previous concept, which proposed a rather unaffected development of G6b-B deficient MKs 2, 4, 8, 20 , and provide an unexpected mechanistic explanation for the severe macrothrombocytopenia in Mpig6b mut mice, as a direct consequence of an overall MK maturation defect. We observed an increased number of immature MKs in the bone marrow, which might help to better understand the cause of myelofibrosis in G6b-B null mice and patients, as an accumulation of immature MKs has been described as the main driver of this complex disease.…”
Section: Resultscontrasting
confidence: 88%
See 3 more Smart Citations
“…3–7 Our results demonstrate a previously unrecognized key function of G6b-B in MK maturation by regulating cell size, DMS development, receptor levels and gene expression. These findings thus challenge the previous concept, which proposed a rather unaffected development of G6b-B deficient MKs 2, 4, 8, 20 , and provide an unexpected mechanistic explanation for the severe macrothrombocytopenia in Mpig6b mut mice, as a direct consequence of an overall MK maturation defect. We observed an increased number of immature MKs in the bone marrow, which might help to better understand the cause of myelofibrosis in G6b-B null mice and patients, as an accumulation of immature MKs has been described as the main driver of this complex disease.…”
Section: Resultscontrasting
confidence: 88%
“…We thus identified a spontaneous single nucleotide mutation within Mpig6b resulting in a phenotype, which faithfully recapitulates Mpig6b -/and Mpig6b diY/F mice. 2,8,9 Analyzing BM-derived MKs from Mpig6b mut mice in vitro, we found that the number of proplatelet-forming cells was significantly reduced compared to the wildtype (WT) (Figure S2ad). The cytoskeleton of proplatelet-forming Mpig6b mut MKs, however, appeared morphologically comparable.…”
Section: Single Nucleotide Exchange In Mpig6b Results In Macrothrombocytopeniamentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7] Based on unaltered ploidy and TPO-induced Erk1/2 activation, reduced proplatelet formation and spreading of Mpig6b -/-MKs in vitro, it was hypothesized that G6b-B does not play a role in MK development, but in a terminal step in platelet production. 2,8 However, the underlying molecular mechanism how this receptor regulates thrombopoiesis remained unknown. By characterizing a spontaneous Mpig6b mutant together with a newly generated Mpig6b-null mouse line we provide unexpected experimental evidence that establishes G6b-B as a central regulator of transcription during MK maturation, which can explain the complex phenotype of these mice.…”
Section: Introductionmentioning
confidence: 99%